Răspunsuri

Cel mai inteligent răspuns!
2014-07-03T10:31:12+03:00
X - 2013 = a
1979 - x = a
⇒ x - 2013 = 1979 - x
    x + x = 1979 + 2013
    2x = 3992
    x = 3992 ÷ 2
    x = 1996
3 3 3
2014-07-03T10:38:49+03:00
A - 2013 = b
1979 - a = b    inlocuim pe b in prima ecuatie
a - 2013 = 1979 - a
2a = 2013 + 1979
2a = 3992
a = 3992 : 2
a = 1996    inlocuim pe a in prima ecuatie
1996 - 2013 = b
- 17 = b
proba :      1996 - 2013 = - 17
                          - 17   = - 17
si              1979 - 1996 = - 17
                            - 17 = - 17                


1 5 1